Investigating English as a Second Language Anxiety among Diploma Students - Apatura, Nanthini; Bahari, Aireen Aina; Samuel Inbaraj, Lisa Malar (Semarak International Journal of Current Research in Language and Human Studies, 2025)
In Malaysia, English is taught as a compulsory second language in all public schools. However, when students move from schools to tertiary institutions where the medium of instruction is English, there is bound to be a feeling of anxiety. Therefore, this research investigates diploma students’ second language anxiety L2 in learning English. It seeks to find out the main factor of anxiety that causes the arousal of anxiety among the students. Also, the study aims to identify the type of anxiety mostly experienced by the students in English learning environment. Finally, the most preferred anxiety coping strategy is also figured out in this study. The instrument used to carry out this study is a questionnaire with a Likert scale ranging from disagree to strongly agree. As a result, the findings of 50 diploma students from higher institutions in Ipoh region revealed that most students appeared to have a high level of perceptions about themselves in learning English and this often are negative beliefs that has made them to feel anxious every time they are in English learning situations. Besides, most of them experienced anxiety in specific situations. The findings on the coping strategies showed that most of the students indicated peer seeking is significantly effective strategy for coping with English as second language anxiety.